A comparative evaluation of retrievability of Guttapercha, Resilon and CPoints for retreatment, using two different rotary retrieval systems - An ex vivo study - Aswathy Prasad; Rajesh Sasidharan Nair; Jeyabalaji Mano Christaine Angelo; Vijay Mathai; R V Vineet; Sarah R Christopher (Wolters Kluwer Medknow Publications, 2018)
Introduction: Nonsurgical retreatment of failure cases requires regaining access to the entire root canal system through complete removal of the core filling material and sealer. Aims: The aim of this study was to compare the retrievability of gutta-percha (GP), Resilon, and CPoints, using Protaper and Mtwo rotary retreatment systems. Materials and Methods: Sixty freshly extracted mandibular premolars were decoronated and biomechanically prepared and obturated using GP, Resilon, and CPoints along with their corresponding sealers, in twenty teeth each. The teeth were divided into 6 groups of 10 teeth each. The filling was removed after 2 weeks with Protaper and Mtwo rotary retreatment files and the teeth were analyzed using cone beam computed tomography, to assess the remaining percentage volume of obturation material from each group. The data were statistically analyzed by ANOVA (post hoc test) followed Dunnett's t-test to evaluate statistical significant between the groups and paired t-test to find statistical significant before and after treatment. Results: The analysis of the results showed that the mean volume percentage of the residual material is low for Resilon group with Protaper retreatment file (16.35 ± 2.69%) and high in the groups obturated by CPoint and removed by Mtwo retreatment file system (29.67 ± 2.34%). Conclusions: Canals obturated with CPoints and endosequence bioceramic sealer are the least retreatable among the study groups.